In2O3 as a promising catalyst for CO2 utilization: A case study with reverse water gas shift over In2O3. Issue 1 (22nd January 2014) - Sun, Qidi; Ye, Jingyun; Liu, Chang‐jun; Ge, Qingfeng
Abstract In2O3 was prepared by using thermal decomposition of indium (III) nitrate hydrate at 300 °C for 3 h. The obtained crystals show a rectangular shape with highly porous morphology. The length of the rectangular In2O3 is ranged from 40 to 80 nm with an average pore diameter of ca. 3.4 nm. Such prepared In2O3 catalyst shows an obviously higher activity for reverse water gas shift (RWGS) than Ga2O3 obtained at the same decomposition temperature. The result is in good agreement with the theoretical prediction, which shows that adsorbed CO2 on In2O3 surface is more highly activated than that on the Ga2O3 surface. The present work confirms that In2O3 is a promising catalyst for not only RWGS but also other CO2 conversion reactions.